Comparison of skeletal muscle mass loss in patients with metastatic colorectal cancer treated with regorafenib or TAS-102 - Hacıoğlu, Muhammet Bekir; Köstek, Osman; Kurt, Nazmi; Küçükarda, Ahmet; Gökyer, Ali; Ustabaşıoğlu, Fethi Emre; Karataş, Fatih; Tunçbilek, Nermin; Uzuno?lu, Sernaz; Bilici, Ahmet; Çiçin, İrfan; Erdoğan, Bülent (Zerbinis Publications, 2019)
Purpose: To assess whether regorafenib and TAS-102 treatments are associated with a change in Skeletal Muscle Area (SMA) as well as to compare Skeletal Muscle Mass (SMM) loss levels between regorafenib and TAS-102 treatments and prognostic significance in the patients with metastatic colorectal cancer (mCRC). Methods: A total of 36 mCRC patients, who received regorafenib or TAS-102 in the third-line and subsequent settings were assessed in the analysis. SMM changes were assessed with CT scans findings, and they were categorized into two groups as SMM-loss (SMM decrease ?2%) and SMM-stable (SMM change <2%). Results: The SMM change after regorafenib therapy was significantly worse compared with TAS-102 therapy (p=0.001). The median overall survival (OS) was longer in SMM-stable group than in SMM-loss group (12.8 months; 95%CI:9.8-15.7) vs. 6.4 months; 95%CI:5.2-7.7, respectively;p=0.04). Cox regression analysis showed that SMM loss was independent prognostic indicator for OS (HR, 2.87; 95%CI: 1.07-7.42, p=0.03). Conclusion: Although patients who received regorafenib had more SMM loss than those who received TAS-102, there was no difference in OS between drugs.
Keywords: Metastatic Colorectal Cancer; Regorafenib; TAS- 102; Sarcopenia; Skeletal Muscle Mass